2018
DOI: 10.1155/2018/2460403
|View full text |Cite
|
Sign up to set email alerts
|

A Mix Design Procedure for Alkali‐Activated High‐Calcium Fly Ash Concrete Cured at Ambient Temperature

Abstract: is research focuses on developing a mix design methodology for alkali-activated high-calcium fly ash concrete (AAHFAC). High-calcium fly ash (FA) from the Mae Moh power plant in northern ailand was used as a starting material. Sodium hydroxide and sodium silicate were used as alkaline activator solutions (AAS). Many parameters, namely, NaOH concentration, alkaline activator solution-to-fly ash (AAS/FA) ratio, and coarse aggregate size, were investigated. e 28-day compressive strength was tested to validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 43 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…Behavior of GPC with nanomaterials was investigated by Phoo-ngernkham et al [ 14 ]. Pozzolanic materials used for GPC mixes were mostly class F fly ash; however, class C fly ash [ 22 ], Phoo-ngernkham et al [ 23 ], natural Pozzolan [ 24 ], ground granulated blast furnace slag (GGBS) [ 25 , 26 ], metakaolin [ 27 , 28 ], rice husk ash [ 29 ], a mixture of two or more Pozzolanic materials [ 30 , 31 , 32 ], and ceramic dust waste [ 33 ] were also examined. Some special ashes or compounds were used by some investigators such as palm oil fuel ash (POFA) [ 34 ], waste bottle glass (WBG) [ 35 ], and sugarcane bagasse ash (SCBA) [ 36 , 37 ].…”
Section: State-of-the-art Review Of Mechanical Properties Of Geopolymer Concretementioning
confidence: 99%
“…Behavior of GPC with nanomaterials was investigated by Phoo-ngernkham et al [ 14 ]. Pozzolanic materials used for GPC mixes were mostly class F fly ash; however, class C fly ash [ 22 ], Phoo-ngernkham et al [ 23 ], natural Pozzolan [ 24 ], ground granulated blast furnace slag (GGBS) [ 25 , 26 ], metakaolin [ 27 , 28 ], rice husk ash [ 29 ], a mixture of two or more Pozzolanic materials [ 30 , 31 , 32 ], and ceramic dust waste [ 33 ] were also examined. Some special ashes or compounds were used by some investigators such as palm oil fuel ash (POFA) [ 34 ], waste bottle glass (WBG) [ 35 ], and sugarcane bagasse ash (SCBA) [ 36 , 37 ].…”
Section: State-of-the-art Review Of Mechanical Properties Of Geopolymer Concretementioning
confidence: 99%
“…Moreover, the strength-based mix design was proposed based on ACI standard (ACI 211.4R-93) [82] with some modifications. This procedure depends on activator to binder ratio, activator concentration, and aggregate gradation [83], as given in Figure 4. modifications.…”
Section: Strength-based MIX Designmentioning
confidence: 99%
“…modifications. This procedure depends on activator to binder ratio, activator concentration, and aggregate gradation [83], as given in Figure 4.…”
Section: Strength-based MIX Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Chindaprasirt al. 2013 [25] produced geopolymer concrete using high calcium, Class C fluidized bed combustion fly ash, cured at 60 • C for 24 h. Phoo-Ngernkham et al [26] showed that the 28-day compressive strength of 15-35 MPa can be obtained using alkali-activated high calcium fly ash concrete cured at ambient temperature (23 ± 1 • C). Further, Diaz et al [27] used three high calcium, Class C fly ashes obtained from power plants around the United States in order to produce geopolymer concrete while it cured for 3 days at 60 • C. Palomo et al [28] produced geopolymer concrete using law calcium Class F fly ashes cured at 65 • C and 85 • C for 24 h, and showed the importance of heat curing, where a significant increase in strength was observed at 85 • C as compared to 65 • C. Moreover, Bakharev [17] developed geopolymer concrete using two Australian low calcium Class F fly ashes cured at 100 • C for 24 h. In the case of brown coal fly ash, Dirgantara et al [15] observed the alkali activation of brown coal fly ash obtained from La Trobe Valley, Victoria, Australia required heat curing of 120 • C for 24 h to optimize the strength development and that the application of lower curing temperatures gave significantly lower compressive strengths.…”
Section: Introductionmentioning
confidence: 99%